2017
DOI: 10.1097/md.0000000000005770
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine prevent postoperative nausea and vomiting on patients during general anesthesia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
71
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 41 publications
11
71
2
Order By: Relevance
“…As an α2 adrenergic receptor agonist, it decreases sympathetic activity by reducing level of catecholamine and/or its opioid-sparing effect (18). Two meta-analysis suggested that administration of dexmedetomidine decrease the incidence of PONV (15,19). This finding was consistent with our study as both MC and FC group has had the higher number of PONV patients, and the number of patients decreased as the dosage of dexmedetomidine increased.…”
Section: Discussionsupporting
confidence: 82%
“…As an α2 adrenergic receptor agonist, it decreases sympathetic activity by reducing level of catecholamine and/or its opioid-sparing effect (18). Two meta-analysis suggested that administration of dexmedetomidine decrease the incidence of PONV (15,19). This finding was consistent with our study as both MC and FC group has had the higher number of PONV patients, and the number of patients decreased as the dosage of dexmedetomidine increased.…”
Section: Discussionsupporting
confidence: 82%
“…Dexmedetomidine is strong, and a highly selective α - 2 agonist that attaches to a transmembrane G - protein coupled receptor in the brain and spinal cord, and affects the function of the central nervous system and the central circulatory system to produce its analgesic and sympathetic effects [ 7 ]. Dexmedetomidine is potentially used in anaesthesia and intensive care units due to its anxiolytic, analgesic, and sympathetic effects as well as its hemodynamic constants [ 7 ] [ 8 ]. Regarding available evidence, PONV is one of the main complaints of surgery and anaesthesia and is one of the risk factors for vomiting after abdominal surgery, such as abdominal hysterectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Bielka K et al found that dexmedetomidine infusion at rate of 0.5 μg/kg/h from induction of anaesthesia to extubation was reduced the incidence of PONV in patients after laparoscopic cholecystectomy (OR 5, 95% CI 1.1-26, p=0.005) [23]. Meta-analyses of clinical trials had similar results, that is, dexmedetomidine infusion during the anesthesia period decreased the incidence of PONV [24]. Suzuki T et al have revealed that patients who were received dexmedetomidine administration had much lower incidence of PONV than those who were received NLA [25].…”
Section: Discussionmentioning
confidence: 91%